Processed soybean in diets for pacu (Piaractus mesopotamicus) - Stech, Marcia Regina; Carneiro, Dalton José [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2015)
Changes in development and in physiological parameters of fingerlings of the pacu(Piaractus mesopotamicus) fed on diets with high levels of integral crude, extruded, toasted soybean and soybean meal were assessed. The products were evaluated in practical diets for pacu, initially weighing 70 ± 2.19 g, during 82 days. Nine treatments were studied in a 2 × 4 + 1 factorial scheme which corresponded to two fish meal protein replacement levels (50 and 100%) and four soybean products, plus control (100% of fish meal - FM). Development, organosomatic indexes and physiological parameters were evaluated. No differences were reported with regard to weight gain, food intake, food conversion, protein efficiency ratio and specific growth rate. A significant interaction was registered for plasma protein between the evaluated ingredients and replacement percentage of fish meal protein. Results showed that the ingredients assessed did not affect the development of the pacu when compared to fish fed on control diet. Protein retention was favored when toasted soybean and when 50% of the diet's protein fraction from fish meal were employed.

O objetivo deste estudo foi avaliar alterações no desenvolvimento e em alguns parâmetros fisiológicos de juvenis de pacu (Piaractus mesopotamicus), alimentados com dietas contendo altas quantidades de soja integral crua, extrusada e tostada e de farelo de soja. Os ingredientes foram avaliados por 82 dias em dietas práticas para pacus com peso inicial de 70 ± 2,19 g. Foram utilizados nove tratamentos em esquema fatorial 2 × 4 + 1, correspondendo a dois níveis de substituição: 50 e 100% da proteína da farinha de peixe e os quatro tipos de soja mais um controle (100% de farinha de peixe). Foram avaliados o desenvolvimento, índices somáticos e os parâmetros fisiológicos. Não foram observadas diferenças significativas para os parâmetros: ganho em peso, consumo de ração, conversão alimentar, retenção de proteína e crescimento específico. Para proteína plasmática foi observada interação significativa entre os ingredientes avaliados e a porcentagem de substituição da proteína da farinha de peixe. Concluiu-se que os diferentes ingredientes avaliados não tiveram efeito sobre o desenvolvimento do pacu, quando comparado com os que consumiram dieta controle, mas os usos de soja tostada e de 50% de proteína proveniente da farinha de peixe favorecem a retenção de proteína nos peixes.
Soja processada em dietas para pacu (Piaractusmesopotamicus)
Keywords: antinutritional factors; body composition; physiology; fatores antinutricionais; composição corporal; fisiologia